Prediksi kesetimbangan adsorpsi uranium pada air dan sedimen pada berbagai pH - Jasmi Budi Utami; Wahyudi Budi Sediawan; Bardi Murachman; Gede Sutresna Wijaya (Jurnal Rekayasa Proses, 2013)
Activities involving uranium as nuclear fuel has potentially polluted the environment. Since uranium is a toxic and radioactive heavy metal, it is necessary to identify its distribution in nature. This study aims to define uranium adsorption equilibrium model in water and sediment. The model is also supposed to be appropriate for various pH of water.Experiments were performed in a batch system. One hundred mL of waste water for National Atomic Energy Agency (BATAN) containing uranium was placed in an erlenmeyer flask and the pH was varied at 3, 5, 7, or 9. Soil was used as adsorbent. The process was shaken at 100 rpm for six hours and then was left for 24 hours to reach the equilibrium. The resulting filtrate was filtered and analyzed using a spectrophotometer.Five different isotherm equilibrium models were proposed in order to fit the equilibrium experimental data. It was found that Chapman equilibrium could fit the data more thoroughly than the other models. From the calculation, it was known that UO22+ parameter values of α, β, γ were 25 mg/g-soil, 2,3 l/mg, and 18,1 respectively, while for (UO2)3(OH)7- were 19 mg/g, 0,095 l/mg, and 3,4 respectively. It is expected that this research will be useful as supporting data for environment impact analysis in nuclear power plants development.